Operator Algebras, Toeplitz Operators and Related Topics - Bauer, Wolfram; Duduchava, Roland; Grudsky, Sergei; Kaashoek, Marinus A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser, 2020)
This book features a collection of up-to-date research papers that study various aspects of general operator algebra theory and concrete classes of operators, including a range of applications. Most of the papers included were presented at the International Workshop on Operator Algebras, Toeplitz Operators, and Related Topics, in Boca del Rio, Veracruz, Mexico, in November 2018. The conference, which was attended by more than 30 leading experts in the field, was held in celebration of Nikolai Vasilevski s 70th birthday, and the contributions are dedicated to him.
Commutative Banach algebras generated by Toeplitz operators on the unit ball -- Toeplitz operators on Fock space: revisiting some old problems -- Laplace-Beltrami equation on surfaces with the Lipschitz boundary -- Reproducing kernels and distinguished metrics -- Fock-Carleson type measures and horizontal Toeplitz operators -- Asymptotics of all eigenvalues of large non self-adjoint Toeplitz Matrices -- A semi-classical limit with applications to Toeplitz algebras -- Solving twofold Ellis-Gohberg inverse problems -- A C*-algebra of nonlocal convolution type operators -- The Maslov index and the spectrum of differential operators -- Toeplitz operators on the unit sphere -- Diagonalization of translation-invariant operators in reproducing kernel Hilbert spaces -- Toeplitz operators and representation theory -- On all but m" families of projections -- Szego theorems for singular Toeplitz operators in the Bargmann space -- Toeplitz operators with radial symbols -- Schrodinger operators with singular potentials supported by unbounded hypersurfaces -- Toeplitz Operators on the Poly-Bergman Spaces of the Upper Half-Plane -- Polyanalytic Spaces -- Algebras Generated by Toeplitz Operator on the Siegel Domain -- On the essential norms of Toeplitz operators -- Making the case for pseudodifferential arithmetic -- Reproducing kernels and Toeplitz operators on Kepler varieties -- Compact quantum surfaces from the Toeplitz algebra -- Sarason's Toeplitz product problem.
Keywords: Operator theory; Operator Theory